Pilot Study to Evaluate the Effect of Topical Dimethicone on Clinical Signs and Skin Barrier Function in Dogs with Naturally Occurring Atopic Dermatitis - C. Pellicoro; R. Marsella; K. Ahrens (Veterinary Medicine International)
This study investigated the effects of a skin protectant solution (dimethicone 2%) on clinical signs and skin barrier function in canine atopic dermatitis (AD). Eighteen dogs with AD were randomly divided into two groups, one received dimethicone and the other received the vehicle (cyclomethicone) on selected areas (pinnae, groin, and axillae) daily for 4 weeks. Owners and investigators were blinded regarding group allocation. Clinical efficacy was evaluated using a scoring system and skin barrier by measuring the transepidermal water loss. Twelve dogs completed the study (50% drop rate in the vehicle and 20% in the dimethicone). For clinical signs, analysis of variance showed an effect of time (; day 0 day 28) and region (axillae groin pinnae) but no effect of group or group × time interaction. For transepidermal water loss, analysis of variance showed only a main effect of region (axillae pinnae groin). Pearson found no correlation between transepidermal water loss and clinical scores. In this pilot study dimethicone had no significant effect on clinical signs and transepidermal water loss in canine atopic dermatitis.